4n(2)-3=2n(2)+9

Simple and best practice solution for 4n(2)-3=2n(2)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4n(2)-3=2n(2)+9 equation:



4n(2)-3=2n(2)+9
We move all terms to the left:
4n(2)-3-(2n(2)+9)=0
We add all the numbers together, and all the variables
-(+2n^2+9)+4n2-3=0
We add all the numbers together, and all the variables
4n^2-(+2n^2+9)-3=0
We get rid of parentheses
4n^2-2n^2-9-3=0
We add all the numbers together, and all the variables
2n^2-12=0
a = 2; b = 0; c = -12;
Δ = b2-4ac
Δ = 02-4·2·(-12)
Δ = 96
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{96}=\sqrt{16*6}=\sqrt{16}*\sqrt{6}=4\sqrt{6}$
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-4\sqrt{6}}{2*2}=\frac{0-4\sqrt{6}}{4} =-\frac{4\sqrt{6}}{4} =-\sqrt{6} $
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+4\sqrt{6}}{2*2}=\frac{0+4\sqrt{6}}{4} =\frac{4\sqrt{6}}{4} =\sqrt{6} $

See similar equations:

| -5.5x+0.56=-2.21 | | 7=2+b | | 3/4=3/8y-1/4 | | 3x+4x+5x=165 | | x+(-16)=-16 | | 329-3x=365 | | 21+15=d-17 | | -6(x+1)-4=22 | | .n-25.4=-44.8 | | 2=3h−7 | | -(x+5)+3x=17 | | -12=-1/2x+8 | | 72+1.5x=68+2× | | 84=99-c | | -7+4r=-25 | | -14-(-v)-(-10v)+(14v)=17 | | 46=18+d | | -6=(n2)-10 | | 9=–2r+5 | | 2(c-13)=-16 | | 12=2(x-7) | | 2(4x-8)=3(x+3) | | -48+40x=32+8 | | x+1.57=9.97 | | x+2x-3=14 | | 7x+27=4x-3 | | v-3.29=6.7 | | 8(b+1)+4=3(2b-8)–16 | | 1.5(2x-4(=2(4x+2) | | 10=-3x+31 | | 3(x+4)=6(-x-1) | | 10=4+1/2x |

Equations solver categories